EFFECT OF WORK COMPLEXITY AND COMPLIANCE PRESSURE ON AUDITOR PERFORMANCE IN HOSPITALITY SERVICE COMPANIES IN THE CITY OF MEDAN - Saraswati, Dwi (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2019)
This study aims to determine the effect of work complexity and compliance pressure on auditor performance in hotel service companies in the city of Medan. The population is auditor employees in the city of Medan. Samples taken were auditor employees at a five-star hotel in the city of Medan. The sampling criteria for auditor staff who were respondents in this study were work experience in FDA of at least one year. The data analysis technique used is the test instrument and multiple linear regression analysis. From the results of multiple linear regression analysis, the Work complexity variable hurts auditor performance. The results of testing the first hypothesis have a negative coefficient of -0.058 with a significance of 0.395 which means that the variable work complexity does not affect the auditor's performance, the second hypothesis states that compliance pressure hurts auditor performance. The analysis shows that the obedience pressure variable has a positive coefficient of 0.033 and a significance value of 0.612 so it is said to reject the second hypothesis. And the value of Adjusted R Square of 0.843 which means that amounted to 84.3% variable auditor performance can be explained by the variable complexity of the work and pressure obedience